Anticancer Potential of Methanol Extract and Fractions of African Leaf (Vernonia amygdalina Del.) Against HeLa Cervical Cancer Cells - Suryati Cintia Gultom; Poppy Anjelisa Zaitun Hasibuan; Denny Satria (Jurnal FARMASIMED (JFM), 2026)
Globally, cervical cancer is one of the leading causes of cancer-related mortality among women. African leaves (Vernonia amygdalina Del.) are known to contain active terpenoid compounds, such as sesquiterpene lactones, which can be utilized for cancer therapy. The aim of this study is to evaluate the cytotoxic potential of methanol extracts and leaf fractions from the African plant as anticancer agents against the HeLa cervical cancer cell line in vitro. The crude African leaf extract was prepared using a reflux method with methanol, followed by liquid-liquid fractionation to obtain n-hexane, chloroform, ethyl acetate, and residual fractions. Cytotoxicity testing was performed using the MTT Assay on HeLa cervical cancer cell lines; samples exhibiting the strongest cytotoxic activity underwent further testing, including cell cycle analysis and apoptosis assays using flow cytometry. The cytotoxicity test results showed that the methanol extract and fractions from African leaves exhibited cytotoxic effects with IC50 values ranging from 25.45 to 4163.63 μg/mL, with the chloroform fraction (IC50 = 25.45 ± 0.97 μg/mL) demonstrating the strongest cytotoxic activity. Cell cycle assay results showed that the chloroform fraction could inhibit HeLa cell proliferation in the G0-G1 phase. Cell apoptosis results indicated that the chloroform fraction could increase total apoptosis by 3.4%. Therefore, African leaves have potential as anticancer candidates, with anticancer active compounds tending to be concentrated in the chloroform fraction. Therefore, African leaves show potential as anticancer agents, with the active anticancer compounds tending to be concentrated in the chloroform fraction. Further studies are urgently needed to isolate and identify the pure compounds from the chloroform fraction of African leaves.